Analisis Pengetahuan, Sikap, Dan Perilaku Anak Buah Kapal Deck Terhadap Penggunaan Personal Protective Equipment Di MV. Sendang Mas - Emaning Galih Titi Lesatri; Sereati Hasugian; Istri Sri Wahyuni (Politeknik Ilmu Pelayaran Semarang, 2020)
This study aims to determine the knowledge, attitudes, and behavior of deck crew regarding the use of Personal Protective Equipment in MV. Sendang Mas. As well as to determine the suitability of knowledge, attitudes and behavior of the deck crew with the applicable rules. The type of research is descriptive with a quantitative approach. With a population of 24 crew on the MV. Sendang Mas by using purposive sampling of the crew of the ship deck, the number of samples in this study were 9 respondents. Retrieval of data obtained from distributing questionnaires, observations of crew members and interviews. The location of this research was carried out when the author was carrying out the practice of sailing on the MV. Sendang Mas. The results showed that the crew of MV. Sendang Mas has a good knowledge of Personal Protective Equipment with the knowledge indicator showing an average score of 3.44. A good attitude about Personal Protective Equipment with the attitude indicator shows an average score of 3.33. As well as having good behavior, with the use of Personal Protective Equipment which reached 98.7%. The knowledge, attitudes and behavior of the deck crew are not maximal and are not in accordance with the Code of Save Working Practice for Merchant Seafarers and SMM TE-S02 regarding Ship Safety Management Procedures for PT. Tirtamas Express.